Axonal Length Determines Distinct Homeostatic Phenotypes in Human iPSC Derived Motor Neurons on a Bioengineered Platform (Adv. Healthcare Mater. 10/2022). Issue 10 (18th May 2022) - Hagemann, Cathleen; Moreno Gonzalez, Carmen; Guetta, Ludovica; Tyzack, Giulia; Chiappini, Ciro; Legati, Andrea; Patani, Rickie; Serio, Andrea
Abstract : Axonal Pathways This cover depicts artistic adaptations of timelapse imaging of human motor axons growing on the bioengineered arrays described in article number 2101817 by Andrea Serio and co‐workers, colorcoded to show how the axon elongation proceeds asynchronously over time.